The Influence of High-Dispersed Barium Titanate, in Films With Addition of, and Based on Poly(Vinylidene) Fluoride), on Structure and Electrophysical Properties of Ones - Dzubenko, L. S.; Makhno, S. M.; Sapyanenko, O. O.; Gorbyk, P. P. (Physics and Chemistry of Solid State, 2017)
With the aim of the creation of effective electret materials, the composite films, based on poly(vinylidene fluoride) (PVF), in addition with segnetoelectric of barium titanate (BaTiO3) were obtained in the concentration range of 0.5 – 5.0 %vol. There are PVF’s melting temperature range becomes narrower, when at 0.5 – 1.0 % vol. of, and, this pointing on more homogeneous crystallite formation by dimensions in. When at high content (5.0 % vol.) of BaTiO3, there is a decrease of crystallization temperature observed (at 5 ºC), and then, there is temperature range broadening exists, and this pointing on forming of larger, but less homogeneous crystallites by dimensions in. It is determined, when composite films of PVF - BaTiO3 , that surface charge is more stable at BaTiO3 content of 4.0 %vol. in, and then, one reaches a value of 10-6 Cl/m2, when at conditions of treatment with electric field and crown discharge, and, at film charge value of 500 kV/m in. There are non-linear dependence of dielectric permittivity exists, either when at low, or very high frequencies, and this may be linked with the influence of high-disperse addition on polymers crystalline structure formation, and sub-surface layers of one.